2020
DOI: 10.1210/clinem/dgaa306
|View full text |Cite|
|
Sign up to set email alerts
|

Osteoporosis in Premenopausal Women: A Clinical Narrative Review by the ECTS and the IOF

Abstract: Abstract Context Consensus regarding diagnosis and management of osteoporosis in premenopausal women (PW) is still lacking due to few studies carried out in this population. Design The European Calcified Tissue Society and the International Osteoporosis Foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 136 publications
1
36
0
3
Order By: Relevance
“…Based on expert opinion, we propose that these women should be offered a baseline fracture risk assessment with evaluation of risk factors and BMD measurement with DXA and VFA. Anti-resorptive therapy can be considered if a Z-score is ≤ -2.0 SD or if a Z-score is between −1.0 and −2.0 and fragility fractures have been reported [92] . Still, dedicated RCTs with a long follow-up are needed in pre-MP women on TAM while it will remain difficult to precisely evaluate anti-fracture benefits in these women due to low fracture incidence.…”
Section: Evaluation Of Fracture Risk and Indication To Initiate Anti-resorptive Therapymentioning
confidence: 99%
“…Based on expert opinion, we propose that these women should be offered a baseline fracture risk assessment with evaluation of risk factors and BMD measurement with DXA and VFA. Anti-resorptive therapy can be considered if a Z-score is ≤ -2.0 SD or if a Z-score is between −1.0 and −2.0 and fragility fractures have been reported [92] . Still, dedicated RCTs with a long follow-up are needed in pre-MP women on TAM while it will remain difficult to precisely evaluate anti-fracture benefits in these women due to low fracture incidence.…”
Section: Evaluation Of Fracture Risk and Indication To Initiate Anti-resorptive Therapymentioning
confidence: 99%
“…However, on the other hand, fracture risk is extremely high in elderly women with GC use and an underlying inflammatory disease, and thus a relative risk reduction of 50-75% of vertebral fractures corresponds with a large reduction in absolute risk. In addition, in postmenopausal women a reduction in fractures was already demonstrated 6 months after initiating alendronate [80]. In other words, the elderly individuals treated with GCs y are the preferred target group for antiosteoporotic drugs.…”
Section: Modern Treatment Of Giop How To Optimize Prevention Of Fractures In Daily Practicementioning
confidence: 98%
“…A previous Egyptian study concluded that TaqI rs731236 has no influence on the risk of T2DM (14) . Moreover, premenopausal osteoporosis and osteoporotic fractures are rare and it occurs often as a secondary disease (18,19) . Accordingly, we aimed to study the influence of VDR TaqI rs731236 A>G on osteoporotic fracture as T2DM complication in Egyptian premenopausal adult females who are matched in their age and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%